Penerapan Model Discovery Learning untuk Meningkatkan Hasil Belajar pada Materi Pengertian Pendapatan Nasional pada Peserta Didik Kelas XII IIS SMA Negeri 1 Parmonangan - Manatap Marasi H Sihombing (Pusat Riset dan Inovasi Nasional, 2024)
This Classroom Action Research was conducted with the aim of knowing the improvement of learning outcomes on the material of Understanding National Income in class XI.IIS SMA Negeri 1 Parmonangan students through the application of the discovery learning learning model.` The research method used in this research is class action research with stages starting from planning learning, implementing, observing and reflecting, which is carried out from cycle I to cycle II and so on until recommendations are obtained, student learning outcomes and classical absorption of students in the last learning cycle are complete. The research subjects in this study were students of class XI.IIS SMA Negeri 1 Parmonangan in the 2022/2023 academic year. The number of students of class XI.IIS SMA Negeri 1 Parmonangan studied was 16 people. The results showed that the activities of students in carrying out the stages of the discovery learning model in economic subjects (Penegrtian and Benefits of National Income) had increased, starting from cycle I to cycle II, namely almost all types of activities were above 70%. The learning outcomes of students have increased while using the discovery learning model. The increase in learning outcomes was seen in the number of participants who reached the KKM increased and increased by 31.25%. The average value of learning outcomes in cycle I was 56.25% and in cycle II the average learning outcomes increased to 87.50%. Then the responses and attitudes of students towards the discovery learning model applied were very positive.